Desenvolvimento e validação de doseamento microbiológico por método de difusão em ágar - cilindros em placas para doripenem pó para solução injetável - Führ, Fernanda (2011)
The carbapenems are a class of -lactam antibiotics that present action against Gram-positive and Gram-negative bacteria. Doripenem is a new carbapenem that has few published studies for the quantitative determination and there isn’t monograph in the Official Codes. Therefore, this study aims to develop and validate microbiological assay for quality control of the drug powder for injectable solution. The parameters analyzed during validation were linearity (r=0.99999), repeatability (RSD=1.74%), intermediate precision (RSD=3.12%), accuracy (98.90 to 101.51%), specificity and robustness. The results show that the method is suitable for quality control of doripenem powder for injectable solution.